2020
DOI: 10.1001/jamanetworkopen.2020.1195
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Outcomes of Young Children After Prenatal Exposure to Medications for Opioid Use Disorder

Abstract: IMPORTANCE The number of children with prenatal opioid exposure to medication for addiction treatment (MAT) with methadone and buprenorphine for maternal opioid use disorder is increasing, but the associations of this exposure with cognitive outcomes are not well understood. OBJECTIVE To examine the strength and consistency of findings in the medical literature regarding the association of prenatal exposure to MAT with early childhood cognitive development, particularly when accounting for variables outside MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 68 publications
0
24
0
3
Order By: Relevance
“…As the POE field progresses, researchers may also want to consider the interaction between other risk factors common among women who use opioids during pregnancy (such as polysubstance exposure, resource limitations, or early life stressors) and POE when developing new translational preclinical models. For instance, a recent systematic review and meta-analysis indicated that nearly 90% of women on medications for OUD (methadone or buprenorphine) also smoked tobacco products during their pregnancy which means isolating prenatal drug exposure to methadone or buprenorphine without tobacco exposure in preclinical models may represent the exception rather than the rule in the clinic ( Nelson et al, 2020 ). These prenatal/postnatal environmental factors may represent possible modulators for the effect of POE on brain and behavioral differences later in life (for further review, see Conradt et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the POE field progresses, researchers may also want to consider the interaction between other risk factors common among women who use opioids during pregnancy (such as polysubstance exposure, resource limitations, or early life stressors) and POE when developing new translational preclinical models. For instance, a recent systematic review and meta-analysis indicated that nearly 90% of women on medications for OUD (methadone or buprenorphine) also smoked tobacco products during their pregnancy which means isolating prenatal drug exposure to methadone or buprenorphine without tobacco exposure in preclinical models may represent the exception rather than the rule in the clinic ( Nelson et al, 2020 ). These prenatal/postnatal environmental factors may represent possible modulators for the effect of POE on brain and behavioral differences later in life (for further review, see Conradt et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of clinical studies have been small, retrospective cohorts which often lack the appropriate controls for factors such as concurrent alcohol, tobacco, or drug use, prenatal care, socioeconomic status, and many other key environmental variables that can impact prenatal and postnatal development. More recent meta-analyses have attempted to correct for these limitations, but the results from these analyses remain somewhat inconsistent which limits our understanding of the ultimate effects of POE on brain and behavioral development ( Baldacchino et al, 2014 ; Yeoh et al, 2019 ; Andersen et al, 2020 ; Nelson et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of prenatal opioid exposure on the developing brain remain poorly understood. Multiple studies on outcomes in opioid-exposed children show adverse effects of maternal opioid use on neurodevelopment, behavior, and vision ( Monnelly et al, 2019 ; Yeoh et al, 2019 ; Andersen et al, 2020 ; Arter et al, 2021 ; Nelson et al, 2020 ; Lee et al, 2020 ). In addition, animal studies show negative effects of maternal opioids on fetal oligodendrocytes and neurons.…”
Section: Introductionmentioning
confidence: 99%
“…The convergence of the escalating opioid epidemic, the COVID-19 pandemic, and systemic and institutional discrimination and violence together represent an acute case of cumulative risk. Their ensuing stress and devastation may permeate virtually all aspects of health, family life, and functioning and further increase disparities, with long-lasting reverberations for decades to come (Dongarwar et al, 2020 ; Nelson et al, 2020 ; Wade, Prime, & Browne, 2020 ). While this will likely have a detrimental neurodevelopmental impact on many children, others will demonstrate resilience and adaptive outcomes (Cicchetti & Curtis, 2007 ; Masten, 2011 ; Masten & Motti-Stefanidi, 2020 ).…”
Section: A Moment In Time Of Great Neurodevelopmental Importancementioning
confidence: 99%